Genetic and physical mapping of the lateral suppressor (ls) locus in tomato - Schumacher, Karin; Ganal, Martin Walter; Theres, Klaus (Molecular genetics and genomics, 1995)
Tomato plants homozygous for the recessive lateral suppressor (ls) mutation show a number of phenotypic abnormalities among which the lack of lateral meristem initiation during vegetative growth and the absence of petals on the flower are the most prominent. As a first step towards the isolation of the Ls gene by means of map-based cloning, we have determined its position on the restriction fragment length polymorphism (RFLP) map of tomato. RFLP analysis of 527 F2 plants segregating for the ls allele allowed us to define an interval of 0.8 cM in which the Ls gene is located. Analysis of the physical distance between the two flanking RFLP markers by pulsed field gel electrophoresis revealed that they lie no further than 375 kb apart. Knowledge of the physical distance together with the availability of a tomato yeast artificial chromosome (YAC) library, makes it feasible to isolate the Ls gene by a map-based cloning approach.